2022
DOI: 10.21037/jtd-22-1524
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of the second predominant subtype in lung adenocarcinoma: a retrospective single-center cohort study

Abstract: Background: The histologic classification of lung adenocarcinoma (LUAD) was mainly divided into three pathological subtype groups: the low-grade predominant subtype group (lepidic), the intermediategrade predominant subtype group (papillary and acinar), and the high-grade predominant subtype group (micropapillary and solid). Previous studies have focused on the prognostic impact of predominant subtypes of lung adenocarcinoma. In this investigation, we investigated the effect of the second predominant subtype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Lung adenocarcinoma (LUAD) is a global lethal malignancy with extensive molecular heterogeneity ( 1 , 2 ). Since 2015, the World Health Organization (WHO) has classified LUAD into inert invasive, microinvasive, and predominantly adnexal.…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinoma (LUAD) is a global lethal malignancy with extensive molecular heterogeneity ( 1 , 2 ). Since 2015, the World Health Organization (WHO) has classified LUAD into inert invasive, microinvasive, and predominantly adnexal.…”
Section: Introductionmentioning
confidence: 99%
“…To get a better explanation for the underlying mechanisms beyond tumorigenesis and malignant discrepancy, several studies were performed to assess the molecular mechanisms and genetic changes of LUAD subtypes, especially on micropapillary lung adenocarcinoma [8][9][10][11]. Two recent studies indicated that patients with micropapillary components had induced the disruption of the catenincadherin complex, contributing to its intracellular adherence [12,13]. In addition, our previous study demonstrated that micropapillary lung adenocarcinoma had a signi cantly higher tumor mutation burden, such as EGFR mutations, ROS1 fusions.…”
Section: Introductionmentioning
confidence: 99%